If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(27 + w) = 74 (27 * 2 + w * 2) = 74 (54 + 2w) = 74 Solving 54 + 2w = 74 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + 2w = 74 + -54 Combine like terms: 54 + -54 = 0 0 + 2w = 74 + -54 2w = 74 + -54 Combine like terms: 74 + -54 = 20 2w = 20 Divide each side by '2'. w = 10 Simplifying w = 10
| 68-3x=33x+16 | | -53-3x=7-9x | | 4x+7=97-5x | | x-4y=5v | | 6x+49=9+13 | | -75-x=8x+15 | | 4x-3=14x-33 | | 6x^2+21x-90= | | 8x+6=3+21 | | 3y^2*4X^2y*5x= | | X^3+10x^2+24x=0 | | (3x-9)=12 | | 55-5x=8x+16 | | -6x=-2x-8 | | 3(2y+1)=14 | | 2(2z+1)-9=29 | | 5x+3=7+7x | | -6p+8+7p=11 | | 50=-2(21-m)+4(m-4) | | X^2+4+4x=0 | | -2x-6=3y-12 | | 2(1-x)=2x+3(2-3x) | | 5x-(x-2)=3(x-4) | | (5v-7)(9+v)=0 | | (9x+8)=9 | | 7x-16=40 | | 3.1x=2.3x+6.4 | | 5x-15=2x-8 | | (9x+8)2=9 | | 13x-(5x-3)=27 | | 6(2x-7)-2(x+3)-16= | | 5(x+4)+3=7x-2(x-5) |